Improving Students' Listening Skill by Using Role-Play Method in the Material of Asking for and Giving Directions - Widiyastuti, Windy; Setyowati, Titik; Wiyaka, Wiyaka (Pascasarjana Universitas PGRI Semarang, 2023)
A communication strategy that enables listeners to comprehend what is said is referred to as listening skills. This enables effective communication to be established as well. This research aimed to improve listening skills in class VII F students of SMPN 6 Semarang for the 2022/2023 academic year in learning English with the material